USE OF MULTIMEDIA TECHNOLOGIES IN UZBEK LANGUAGE CLASSES (E Global Congress, 2023)
This article discusses the effective use of multimedia tools in Uzbek language classes, multimedia technology and requirements for creating assignments and their implementation. Computer programmers may have sufficient knowledge and experience on the quality of the product to be created, but cannot fully meet the methodological requirements. Therefore, modern native language teachers should acquire not only their specialties, but also the ability to create software multimedia products.